Institutional dynamics, stakeholder interactions, and sustainability pathways in North Toraja's Arabica coffee sector: a systems approach to inclusive agribusiness transformation - Astaman, Putra; Darma, Rahim; Azkar, Riad; Kamarulzaman, Nitty Hirawaty; Bakheet Ali, Hamed Norolla; Amandaria, Riri; Viantika, Ni Made; Hikmah, Aulia Nurul (Frontiers Media SA, 2026)
Introduction: North Toraja's Arabica coffee sector—recognized for its distinctive quality and protected by Geographical Indication (GI) status—continues to face sustainability challenges shaped by institutional dynamics, power asymmetries, and socio-cultural contexts. Despite strong international demand, smallholder farmers contend with aging plantations, climate variability, weak bargaining power, and fragmented governance that constrain access to resources and influence over decision-making. Methods: This study adopts a systems thinking approach using interpretive structural modeling (ISM) to examine stakeholder interactions, map systemic constraints, and identify leverage points for inclusive transformation. Data were collected through in-depth interviews, expert questionnaires, and field observations involving farmers, cooperatives, traders, small and medium enterprises, and government agencies, and were supplemented with secondary sources. Results: The ISM results indicate that upstream institutional strategies—particularly minimum price guarantees and certified seed systems—exert the strongest driving power, shaping the feasibility of downstream initiatives across the value chain. Conversely, interventions such as youth engagement, post-harvest innovation, and digital marketing show high dependence on enabling governance, coordinated action, and sustained institutional support. Key barriers include intermediary dominance and the absence of sustained cross-actor collaboration. Discussion: These findings suggest that sustainable transformation requires linking top-down governance reforms with bottom-up empowerment to rebalance bargaining power and strengthen local agency. Multi-stakeholder platforms, inclusive decision-making processes, and context-sensitive institutional arrangements can improve coordination and unlock dependent initiatives. As a novel contribution, the study moves beyond descriptive stakeholder mapping by structurally ranking sustainability interventions and barriers according to their driving-dependence relationships, thereby identifying actionable institutional leverage points for GI-protected, smallholder coffee value chains. By integrating institutional, social, and economic perspectives, this study advances a sociologically grounded framework for agribusiness transformation, offering transferable insights for other smallholder-dominated commodity systems in the Global South.